ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI PERSEPSI PENGUSAHA UMKM TERHADAP LAPORAN KEUANGAN BERBASIS SAK ETAP DI KABUPATEN INDRAGIRI HILIR - ADINDA PRATIWI, PUTRI; GUSTINA, IRA; NURFITRIANI, NURFITRIANI (Fakultas Ekonomi Universitas Islam Indragiri, 2024)
The post-COVID-19 pandemic has impacted various sectors, one of which is Micro, Small, and Medium Enterprises (MSMEs), also causing a decline in the national economy. This research aims to empirically determine and test the influence of Business Turnover, Business Duration, Information Technology Utilization, and Accounting Comprehension on the Perception of MSME Entrepreneurs in Indragiri Hilir Regency. The sample of this study consists of 37 MSMEs in the small and medium industry sector in Tembilahan City District, Indragiri Hilir Regency, Riau. The type of research used in this study is descriptive qualitative research. The analytical technique used is multiple linear regression. The results of the hypothesis test partially show that Business Turnover does not affect the Perception of MSME Entrepreneurs, while Business Duration, Information Technology Utilization, and Accounting Comprehension do affect the Perception of MSME Entrepreneurs about financial reports based on SAK ETAP in Indragiri Hilir Regency